PREPARATION OF EXTRACTS BASED ON CRATAEGUS FLABELLATA FRUITS - Usmanova Markhabo Balkhievna; Toyirova Niginabonu; Zaypullayeva Gulsanam (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The total flavonoid content of hawthorn fruits, expressed as catechin, is 3.75 ± 0.15% in the dried fruit, 4.65 ± 0.05% in the thick extract, and 1.07 ± 0.18% in  the  liquid  extract.  Crataegus  flabellatа  fruits,  along  with  other  pharmacopoeial species,  represent  a  promising  source  of  biologically  active  substances  for  the development of drugs.